2.2.30 Problems 2901 to 3000

Table 2.61: Main lookup table. Sorted sequentially by problem number.

#

ODE

CAS classification

Solved?

time (sec)

2901

\[ {}x -y+1+\left (x -y-1\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.773

2902

\[ {}x +2 y+\left (3 x +6 y+3\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.838

2903

\[ {}x +2 y+2 = \left (2 x +y-1\right ) y^{\prime } \]

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

5.142

2904

\[ {}3 x -y+1+\left (x -3 y-5\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

13.116

2905

\[ {}6 x -3 y+6+\left (2 x -y+5\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.391

2906

\[ {}2 x +3 y+2+\left (y-x \right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1460.432

2907

\[ {}x +y+4 = \left (2 x +2 y-1\right ) y^{\prime } \]
i.c.

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.347

2908

\[ {}2 x +3 y-1+\left (2 x +3 y+2\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.320

2909

\[ {}3 x -y+2+\left (x +2 y+1\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

5.477

2910

\[ {}3 x +2 y+3-\left (x +2 y-1\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

49.512

2911

\[ {}x -2 y+3+\left (1-x +2 y\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.233

2912

\[ {}2 x +y+\left (4 x +2 y+1\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.207

2913

\[ {}2 x +y+\left (4 x -2 y+1\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class C‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

85.084

2914

\[ {}x +y+\left (x -2 y\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

5.010

2915

\[ {}3 x +y+\left (x +3 y\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

4.881

2916

\[ {}a_{1} x +b_{1} y+c_{1} +\left (b_{1} x +b_{2} y+c_{2} \right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class C‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

3.700

2917

\[ {}x \left (6 x y+5\right )+\left (2 x^{3}+3 y\right ) y^{\prime } = 0 \]

[_exact, _rational, [_1st_order, ‘_with_symmetry_[F(x),G(x)]‘], [_Abel, ‘2nd type‘, ‘class A‘]]

1.337

2918

\[ {}3 x^{2} y+x y^{2}+{\mathrm e}^{x}+\left (x^{3}+x^{2} y+\sin \left (y\right )\right ) y^{\prime } = 0 \]

[_exact]

2.050

2919

\[ {}2 x y-\left (x^{2}+y^{2}\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _rational, _dAlembert]

5.181

2920

\[ {}y \cos \left (x \right )-2 \sin \left (y\right ) = \left (2 x \cos \left (y\right )-\sin \left (x \right )\right ) y^{\prime } \]

[_exact]

10.455

2921

\[ {}\frac {2 x y-1}{y}+\frac {\left (x +3 y\right ) y^{\prime }}{y^{2}} = 0 \]

[[_homogeneous, ‘class D‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.934

2922

\[ {}y \,{\mathrm e}^{x}-2 x +{\mathrm e}^{x} y^{\prime } = 0 \]

[[_linear, ‘class A‘]]

1.737

2923

\[ {}3 y \sin \left (x \right )-\cos \left (y\right )+\left (x \sin \left (y\right )-3 \cos \left (x \right )\right ) y^{\prime } = 0 \]

[_exact]

39.391

2924

\[ {}x y^{2}+2 y+\left (2 y^{3}-x^{2} y+2 x \right ) y^{\prime } = 0 \]

[_rational]

1.461

2925

\[ {}\frac {2}{y}-\frac {y}{x^{2}}+\left (\frac {1}{x}-\frac {2 x}{y^{2}}\right ) y^{\prime } = 0 \]

[_separable]

1.914

2926

\[ {}\frac {x y+1}{y}+\frac {\left (2 y-x \right ) y^{\prime }}{y^{2}} = 0 \]

[[_homogeneous, ‘class D‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.698

2927

\[ {}\frac {y \left (2+x^{3} y\right )}{x^{3}} = \frac {\left (1-2 x^{3} y\right ) y^{\prime }}{x^{2}} \]

[[_homogeneous, ‘class G‘], _exact, _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

2.546

2928

\[ {}y^{2} \csc \left (x \right )^{2}+6 x y-2 = \left (2 y \cot \left (x \right )-3 x^{2}\right ) y^{\prime } \]

[_exact, [_Abel, ‘2nd type‘, ‘class B‘]]

52.042

2929

\[ {}\frac {2 y}{x^{3}}+\frac {2 x}{y^{2}} = \left (\frac {1}{x^{2}}+\frac {2 x^{2}}{y^{3}}\right ) y^{\prime } \]

[[_homogeneous, ‘class G‘], _exact, _rational]

3.108

2930

\[ {}\cos \left (y\right )-\left (x \sin \left (y\right )-y^{2}\right ) y^{\prime } = 0 \]

[_exact, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

5.158

2931

\[ {}2 y \sin \left (x y\right )+\left (2 x \sin \left (x y\right )+y^{3}\right ) y^{\prime } = 0 \]

[_exact]

42.911

2932

\[ {}\frac {x \cos \left (\frac {x}{y}\right )}{y}+\sin \left (\frac {x}{y}\right )+\cos \left (x \right )-\frac {x^{2} \cos \left (\frac {x}{y}\right ) y^{\prime }}{y^{2}} = 0 \]

[_exact]

5.923

2933

\[ {}y \,{\mathrm e}^{x y}+2 x y+\left (x \,{\mathrm e}^{x y}+x^{2}\right ) y^{\prime } = 0 \]

[_exact]

2.140

2934

\[ {}\frac {x^{2}+3 y^{2}}{x \left (3 x^{2}+4 y^{2}\right )}+\frac {\left (2 x^{2}+y^{2}\right ) y^{\prime }}{y \left (3 x^{2}+4 y^{2}\right )} = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

20.906

2935

\[ {}\frac {x^{2}-y^{2}}{x \left (2 x^{2}+y^{2}\right )}+\frac {\left (x^{2}+2 y^{2}\right ) y^{\prime }}{y \left (2 x^{2}+y^{2}\right )} = 0 \]

[[_homogeneous, ‘class A‘], _exact, _rational, _dAlembert]

26.920

2936

\[ {}\frac {2 x^{2}}{x^{2}+y^{2}}+\ln \left (x^{2}+y^{2}\right )+\frac {2 x y y^{\prime }}{x^{2}+y^{2}} = 0 \]

[_exact]

1.831

2937

\[ {}y^{\prime } x +\ln \left (x \right )-y = 0 \]

[_linear]

1.146

2938

\[ {}x y+\left (y+x^{2}\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

2.362

2939

\[ {}\left (x -2 x y\right ) y^{\prime }+2 y = 0 \]

[_separable]

1.885

2940

\[ {}x^{2} y+y^{2}+x^{3} y^{\prime } = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Bernoulli]

1.950

2941

\[ {}x y^{3}-1+x^{2} y^{2} y^{\prime } = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Bernoulli]

2.827

2942

\[ {}\left (x^{3} y^{3}-1\right ) y^{\prime }+x^{2} y^{4} = 0 \]

[[_homogeneous, ‘class G‘], _rational]

2.277

2943

\[ {}y \left (y-x^{2}\right )+x^{3} y^{\prime } = 0 \]

[[_homogeneous, ‘class D‘], _rational, _Bernoulli]

2.166

2944

\[ {}y+x y^{2}+\left (x -x^{2} y\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.750

2945

\[ {}\left (x -x \sqrt {x^{2}-y^{2}}\right ) y^{\prime }-y = 0 \]

[‘y=_G(x,y’)‘]

4.139

2946

\[ {}2 x y+\left (y-x^{2}\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

1.657

2947

\[ {}y = x \left (x^{2} y-1\right ) y^{\prime } \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

6.647

2948

\[ {}{\mathrm e}^{x} y^{\prime } = 2 x y^{2}+y \,{\mathrm e}^{x} \]

[_Bernoulli]

2.288

2949

\[ {}\left (x^{2}+y^{2}+x \right ) y^{\prime } = y \]

[_rational]

1.206

2950

\[ {}\left (2 x +3 x^{2} y\right ) y^{\prime }+y+2 x y^{2} = 0 \]

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

1.974

2951

\[ {}2 x^{2} y y^{\prime }+x^{4} {\mathrm e}^{x}-2 x y^{2} = 0 \]

[[_homogeneous, ‘class D‘], _Bernoulli]

1.944

2952

\[ {}y \left (1-x^{4} y^{2}\right )+y^{\prime } x = 0 \]
i.c.

[[_homogeneous, ‘class G‘], _rational, _Bernoulli]

2.924

2953

\[ {}y \left (x^{2}-1\right )+x \left (x^{2}+1\right ) y^{\prime } = 0 \]
i.c.

[_separable]

2.165

2954

\[ {}x^{2} y^{2}-y+\left (2 x^{3} y+x \right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class G‘], _rational, [_Abel, ‘2nd type‘, ‘class B‘]]

3.101

2955

\[ {}\left (x^{2}+y^{2}-2 y\right ) y^{\prime } = 2 x \]
i.c.

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

1.419

2956

\[ {}y-x^{2} \sqrt {x^{2}-y^{2}}-y^{\prime } x = 0 \]
i.c.

[[_1st_order, ‘_with_symmetry_[F(x),G(x)*y+H(x)]‘]]

36.641

2957

\[ {}y \left (x +y^{2}\right )+x \left (x -y^{2}\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class G‘], _rational]

193.409

2958

\[ {}y^{\prime } x +2 y = x^{2} \]

[_linear]

1.668

2959

\[ {}y^{\prime }-x y = {\mathrm e}^{\frac {x^{2}}{2}} \cos \left (x \right ) \]

[_linear]

1.710

2960

\[ {}y^{\prime }+2 x y = 2 x \,{\mathrm e}^{-x^{2}} \]

[_linear]

2.463

2961

\[ {}y^{\prime } = y+3 x^{2} {\mathrm e}^{x} \]

[[_linear, ‘class A‘]]

1.694

2962

\[ {}x^{\prime }+x = {\mathrm e}^{-y} \]

[[_linear, ‘class A‘]]

1.171

2963

\[ {}y x^{\prime }+\left (1+y \right ) x = {\mathrm e}^{y} \]

[_linear]

1.366

2964

\[ {}y+\left (2 x -3 y\right ) y^{\prime } = 0 \]

[[_homogeneous, ‘class A‘], _rational, [_Abel, ‘2nd type‘, ‘class A‘]]

5.743

2965

\[ {}y^{\prime } x -2 x^{4}-2 y = 0 \]

[_linear]

1.603

2966

\[ {}1 = \left ({\mathrm e}^{y}+x \right ) y^{\prime } \]

[[_1st_order, _with_exponential_symmetries]]

1.275

2967

\[ {}y^{2} x^{\prime }+\left (y^{2}+2 y \right ) x = 1 \]

[_linear]

2.173

2968

\[ {}y^{\prime } x = 5 y+x +1 \]

[_linear]

1.740

2969

\[ {}x^{2} y^{\prime }+y-2 x y-2 x^{2} = 0 \]

[_linear]

1.697

2970

\[ {}\left (x +1\right ) y^{\prime }+2 y = \frac {{\mathrm e}^{x}}{x +1} \]

[_linear]

1.728

2971

\[ {}\cos \left (y\right )^{2}+\left (x -\tan \left (y\right )\right ) y^{\prime } = 0 \]

[[_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

4.088

2972

\[ {}2 y = \left (y^{4}+x \right ) y^{\prime } \]

[[_homogeneous, ‘class G‘], _rational]

2.463

2973

\[ {}\cos \left (\theta \right ) r^{\prime } = 2+2 r \sin \left (\theta \right ) \]

[_linear]

1.952

2974

\[ {}\sin \left (\theta \right ) r^{\prime }+1+r \tan \left (\theta \right ) = \cos \left (\theta \right ) \]

[_linear]

5.210

2975

\[ {}y x^{\prime } = 2 y \,{\mathrm e}^{3 y}+x \left (3 y +2\right ) \]

[_linear]

1.992

2976

\[ {}y^{2}+1+\left (2 x y-y^{2}\right ) y^{\prime } = 0 \]
i.c.

[_exact, _rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

3.274

2977

\[ {}y^{\prime }+y \cot \left (x \right )-\sec \left (x \right ) = 0 \]

[_linear]

1.668

2978

\[ {}y+y^{3}+4 \left (x y^{2}-1\right ) y^{\prime } = 0 \]
i.c.

[_rational, [_1st_order, ‘_with_symmetry_[F(x)*G(y),0]‘]]

1.802

2979

\[ {}2 y-x y-3+y^{\prime } x = 0 \]
i.c.

[_linear]

1.566

2980

\[ {}y+2 \left (x -2 y^{2}\right ) y^{\prime } = 0 \]
i.c.

[[_homogeneous, ‘class G‘], _rational]

5.169

2981

\[ {}\left (x^{2}-1\right ) y^{\prime }+\left (x^{2}-1\right )^{2}+4 y = 0 \]
i.c.

[_linear]

1.680

2982

\[ {}3 y^{2} y^{\prime }-x y^{3} = {\mathrm e}^{\frac {x^{2}}{2}} \cos \left (x \right ) \]

[_Bernoulli]

3.391

2983

\[ {}y^{3} y^{\prime }+x y^{4} = x \,{\mathrm e}^{-x^{2}} \]

[_Bernoulli]

3.491

2984

\[ {}\cosh \left (y\right ) y^{\prime }+\sinh \left (y\right )-{\mathrm e}^{-x} = 0 \]

[‘y=_G(x,y’)‘]

2.169

2985

\[ {}\sin \left (\theta \right ) \theta ^{\prime }+\cos \left (\theta \right )-t \,{\mathrm e}^{-t} = 0 \]

[‘y=_G(x,y’)‘]

2.587

2986

\[ {}x y y^{\prime } = x^{2}-y^{2} \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

4.851

2987

\[ {}y^{\prime }-x y = \sqrt {y}\, x \,{\mathrm e}^{x^{2}} \]

[_Bernoulli]

1.495

2988

\[ {}t x^{\prime }+x \left (1-x^{2} t^{4}\right ) = 0 \]

[[_homogeneous, ‘class G‘], _rational, _Bernoulli]

2.601

2989

\[ {}x^{2} y^{\prime }+y^{2} = x y \]

[[_homogeneous, ‘class A‘], _rational, _Bernoulli]

2.375

2990

\[ {}\csc \left (y\right ) \cot \left (y\right ) y^{\prime } = \csc \left (y\right )+{\mathrm e}^{x} \]

[‘y=_G(x,y’)‘]

2.532

2991

\[ {}y^{\prime }-x y = \frac {x}{y} \]

[_separable]

1.809

2992

\[ {}y+y^{\prime } x = y^{2} x^{2} \cos \left (x \right ) \]

[_Bernoulli]

3.296

2993

\[ {}r^{\prime }+\left (r-\frac {1}{r}\right ) \theta = 0 \]

[_separable]

1.782

2994

\[ {}y^{\prime } x +2 y = 3 x^{3} y^{{4}/{3}} \]

[[_homogeneous, ‘class G‘], _rational, _Bernoulli]

7.212

2995

\[ {}3 y^{\prime }+\frac {2 y}{x +1} = \frac {x}{y^{2}} \]

[_rational, _Bernoulli]

2.355

2996

\[ {}\cos \left (y\right ) y^{\prime }+\left (\sin \left (y\right )-1\right ) \cos \left (x \right ) = 0 \]

[_separable]

40.341

2997

\[ {}\left (x \tan \left (y\right )^{2}+x \right ) y^{\prime } = 2 x^{2}+\tan \left (y\right ) \]

[‘y=_G(x,y’)‘]

1.755

2998

\[ {}y^{\prime }+y \cos \left (x \right ) = y^{3} \sin \left (x \right ) \]

[_Bernoulli]

3.180

2999

\[ {}y^{\prime }+y = y^{2} {\mathrm e}^{-t} \]
i.c.

[[_1st_order, _with_linear_symmetries], _Bernoulli]

1.685

3000

\[ {}y^{\prime } = x \left (1-{\mathrm e}^{2 y-x^{2}}\right ) \]
i.c.

[[_1st_order, ‘_with_symmetry_[F(x),G(y)]‘]]

2.088